J/ψ photoproduction and polarization in peripheral Pb−Pb collisions with ALICE - Mallick Dukhishyam (EPJ Web of Conferences)
Ultrarelativistic heavy-ion collisions generate a powerful electromagnetic field that produces photonuclear reactions. These processes have been extensively studied in ultraperipheral collisions, in which the impact parameter is larger than twice the nuclear radius. Recently, coherent photoproduction of J/ψ has been observed in nucleus–nucleus (A–A) collisions with nuclear overlap, based on the measurement of an excess of production with respect to hadron-production expectations in the very low transverse momentum (pT). Such quarkonium measurements provide valuable information about the nuclear gluon distribution at low Bjorken x and high energy. In addition, they can constrain the theory describing photon-induced reactions in A–A collisions with nuclear overlap, including possible interactions of the measured probes with the formed and fast expanding Quark-Gluon Plasma. In order to confirm the photoproduction origin of the very low pT J/ψ yield excess, polarization measurements represent a suitable observable. It is expected that the produced quarkonium inherits the polarization of the incoming photon because of the s-channel helicity conservation. ALICE can measure inclusive and exclusive quarkonium production down to pT = 0, at forward rapidity (2.5 < y < 4) and midrapidity (|y| < 0.9). In this contribution, new preliminary measurement of the y-differential cross section and the first new polarization analysis at the LHC of coherently photoproduced J/ψ in peripheral Pb–Pb collisions will be presented. These measurements are conducted at forward rapidity in the dimuon decay channel. These results will be discussed together with the recent results on coherent photoproduction as a function of centrality at both mid and forward rapidities. Comparison with models will be shown whenever available.